Opportunities and potential of small indigenous fish species in the East Kolkata wetlands, India - Sathiskumar, Abinaya; Saha, Dipankar; Karnatak, G.; Chakrabarti, A.; Molla, S.; Samanta, S.; Das, B. K.; Roy, M. N.; Taron, Avinandan (International Water Management Institute, 2025)
Small Indigenous Fish Species (SIS) have historically been undervalued in the East Kolkata Wetlands (EKW) despite their high nutritional value, ecological importance, and livelihood contributions. Emerging evidence demonstrates that SIS play a critical role in enhancing pond productivity, nutrient cycling, and household food security, especially for low-income and wetland-dependent communities. The study underscores targeted policy support, capacity-building, financial access to scale production, and access to quality seeds for small farmers to adapt and rejuvenate SIS cultivation.